Demographic Trends in Paddle Lead Spinal Cord Stimulator Placement: Private Insurance and Medicare Beneficiaries - Lawal Labaran; Joshua Bell; Varun Puvanesarajah; Nikhil Jain; Jomar N. Aryee; Micheal Raad; Amit Jain; Jonathan Carmouche; Hamid Hassanzadeh (Neurospine, 2020)
Objective Although spinal cord stimulators (SCS) continue to gain acceptance as a viable nonpharmacologic option for the treatment of chronic back pain, recent trends are not well established. The aim of this study was to evaluate recent overall demographic and regional trends in paddle lead SCS placement and to determine if differences in trends exist between private-payer and Medicare beneficiaries. Methods A retrospective review of Medicare and private-payer insurance records from 2007–2014 was performed to identify patients who underwent a primary paddle lead SCS placement via a laminectomy (CPT-63655). Each study cohort was queried to determine the annual rate of SCS placements and demographic characteristics. Yearly SCS implantation rates within the study cohorts were adjusted per 100,000 beneficiaries. A chi-square analysis was used to compare changes in annual rates. Results A total of 31,352 Medicare and 2,935 private-payer patients were identified from 2007 to 2014. Paddle lead SCS placements ranged from 5.9 to 17.5 (p < 0.001), 1.9 to 5.9 (p < 0.001), and 5.2 to 14.5 (p < 0.001) placements per 100,000 Medicare, private-payer, and overall beneficiaries respectively from 2007 to 2014. SCS placements peaked in 2013 with 19.6, 7.1, and 16.8 placements per 100,000 Medicare, private-payer, and overall patients. Conclusion There was an overall increase in the annual rate of SCS placements from 2007 to 2014. Paddle lead SCS placements peaked in 2013 for Medicare, private-payer, and overall beneficiaries. The highest incidence of implantation was in the Southern region of the United States and among females. Yearly adjusted rates of SCSs were higher among Medicare patients at all time points.